Beyond Perceived Usefulness: Trust as a Generative Mechanism in AI-Driven Epistemic Transformation in Educational Management - Efrita Norman; Armanparamansyah; Yanti Hasbian Setia wati; Enah pahlawan (Al-Qalam Institue, 2026)
This study aims to reposition the adoption of generative artificial intelligence (AI) in education as an epistemic transformation process by examining how digital literacy shapes multidimensional trust and how such trust mediates creativity as an expression of epistemic agency within educational management contexts. A constructivist grounded theory approach was employed, involving 24 participants. Data were collected through in-depth interviews, focus group discussions, and analysis of AI-assisted academic tasks, and analyzed using open, axial, and selective coding with a constant comparative method. The findings reveal differentiated dimensions of digital literacy (operational, evaluative, reflective, and strategic) that produce layered forms of trust (functional, relational, and epistemic). Only reflective epistemic trust was found to stimulate generative creativity, while functional trust tended to result in reproductive use of AI. The study proposes a conceptual model of “Reflexive TrustMediated Epistemic Agency,” positioning trust as a generative mechanism linking digital literacy and creative transformation. The implications highlight the need for educational management to move beyond utility-based adoption frameworks by fostering evaluative and reflective digital literacy, ensuring that AI serves as a catalyst for meaningful learning transformation rather than merely a productivity tool.